Identification of Candida spp. isolated from vaginal swab by phenotypic methods and multiplex PCR in Duhok, Iraq - Mohammed, Ahmed Basheer; Ali, Jumma Hussein; Abdullah, Samir Khalaf (International Journal of Research in Medical Sciences, 2017)
Background: Candida species are the second most common cause of vulvovaginitis worldwide. The purpose of this study was to identify the species of vaginal Candida isolates by using phenotypic and Multiplex PCR techniques. Methods: 91 isolates from patients admitted to Azadi hospital and Maternity hospital in Duhok city were collected. The vaginal swab specimens were inoculated on Sabouraud dextrose agar. Colonies were then sub cultured on Chromogenic Candida agar. Genomic DNA extraction was performed using a Genomic DNA Extraction kit. For rapid identification of Candida spp., specific primers based on the genomic sequence of DNA topoisomerase 11 of C. albicans, C. parapsilosis I, C. parapsilosis II, C. guilliermondi, C. dubliniensis, C. krusei, C. kefyr and C. glabrata, C. tropicalis I, C. tropicalis II, C. lusitaniae were used. The multiplex PCR products were separated by electrophoresis in 1.5% agarose gel, visualized by staining with ethidium bromide, and photographed. Results: 4 Candida species, namely C. albicans, C. glabrata, C. krusei and C. tropicalis were distinguished by Chromogenic Candida agar on the basis of colony colour and morphology. PCR with the primer mixes yielded 7 different sized of PCR products corresponding to C. albicans, C. guilliermondii, C. dubliniensis, C. glabrata, C. kefyr, C. krusei and C. tropicalis II. The analysis revealed C. glabrata and C. albicans were the most common species isolated with the percentage 40% and 30% respectively. Conclusions: This study concluded that phenotypic characteristics on selective agar medium such as chromogenic candida agar are useful for presumptive identification of Candiada spp. with the support of molecular method such as multiplex PCR.